Lost to Presence: The Entanglements of Writing, Protestant Christianity, and Empire in the 19th-Century Southern Africa - Sepetla Molapo (Journal for the Study of Religion)
This essay takes interest in a dialectical relationship between writing as affir-mation and writing as a system of codification. It explores this dialectic as it relates to the interaction between Sotho-speaking communities and Protestant Christian missionaries in the 19th-century Southern Africa. It shows that this dialectical relationship dissolves truth as a construct of writing as affirmation because it is informed by an ontology of force that conceives of truth (Christian truth in this case) as an outcome of victory over an adversary. This ontology of force, in which Christianity participates, is a consequence of a modern metaphysics that splits individual and divine will. Cut off from participation in divine will, the autonomous will of Protestant Christian missionaries became the basis for organizing the world of the 19th-century Sotho speakers. This opened doors for Christianity to participate in the broader imperial project of the racial subordination of colonized people that Sotho speakers resemble. The consequence of this was not only the delegitimization of personhood as a construct of indigenous African religion, but also the introduction of conceptions of personhood that partook of race and racism.